Bibliografinių nuorodų panaudojimas, vertinant mokslinę veiklą - Motiekienė, Vilija (Knygotyra, 1985)
The statistical analysis of the system of citation is one of the most popular methods, studying the development of science. The wide use of such analysis in various spheres of science and the popularity of such publications as “Science Citation Index” show the facts in favour of this method. We must stress, that with the help of this analysis we can determine objectively enough the quality of the scientific activities.The Lithuanian authors published several articles about the analysis of citation. One of these articles stresses that the citation of a given scientific publication which is revealed with the help of analysis of citation, is the most objective criterion for the evaluation of this publication.On the basis of this statement an experiment was organized about the citation of publications of Lithuanian scientists, whose articles were published in the journal “Scientific Technical Information” in 1961–1973.The experimental results turned out to be interesting enough, though the final conclusions on this statement must be made after a series of other experiments on the basis of more comprehensive material.